Diversity Identity Management: An Organizational Perspective - Cole, Brooklyn M. (Journal of business ethics, 2013)
Organizations are faced with the challenge of responding to increasing pressures to promote diversity in various ways. We draw attention to one possible proactive organizational response—the incorporation of diversity in organizational identity. This initial response necessarily evokes subsequent tasks of managing the changed identity. Therefore, this article also addresses the management of diversity identity within organizations, and relevant organizational outcomes. Our theoretical model is grounded in institutional theory, and we propose that the management of diversity identity can impact both perceptions of legitimacy as well as diversity identity. Adequate, inadequate, and optimal management of diversity identity have differential effects on legitimacy and diversity identity. We contribute to the literature by a) unbundling initial and later firm responses to promoting diversity at the organizational level, and b) offering a more nuanced understanding of the complexities of managing diversity identity within organizations.